Building Law-Knowledgeable Citizens through Civic Education in the Era of Globalisation - Anshori, Ibnu; Rahmawati, Alfi Mufida; Putra, Rizky Perdana Bayu (Universitas Kristen Cipta Wacana, 2025)
This research aims to explore the role of civic education in building law-aware citizens in the era of globalisation. Using a qualitative approach with a literature review, this research examines relevant literature related to civic education, law, and globalisation. The findings show that civic education plays an important role in shaping students' legal character through teaching that integrates national and international legal knowledge. Globalisation brings challenges in ensuring the accuracy of legal information received by students, so legal literacy and critical thinking skills become important aspects in civic education. Problem-based learning (PBL) and case study methods have proven effective in improving students' understanding of the application of law. In addition, the integration of global legal literacy in civic education is very relevant to prepare students for international legal issues. This research recommends strengthening the civic education curriculum by introducing international law, using technology to support learning, and implementing interactive teaching methods to improve students' 21st century skills. Thus, civic education is expected to form law-savvy citizens, both at the national and international levels.